Your project management coach : best practices for managing projects in the real world - Biafore, Bonnie; Stover, Teresa S. (Indianapolis, Indiana : John Wiley & Sons, 2012)
A pragmatic approach to project management Many projects fail to deliver on time or on budget, or even to deliver a workable product that satisfies the customer. While good project management goes a long way towards ensuring success, managers often fail to follow the plans they implement
1. Understanding Projects and Project Management -- 2. Planning a Project -- 3. Executing a Project -- 4. Monitoring and Controlling -- 5. Closing the Project -- 6. Taking the Next Steps in Project Management
Includes index
Keywords: Project management